Immunoreactivity of the SARS-CoV-2 entry proteins ACE-2 and TMPRSS-2 in murine models of hormonal manipulation, ageing, and cardiac injury - Susan Bengs; Alexia Rossi; Martina Haberecker; Nidaa Mikail; Alexander Meisel; Achi Haider; Muriel Grämer; Angela Portmann; Atanas Todorov; Christof Schönenberger; Caroline E. Gebhard; Gabriela M. Kuster; et al. (Scientific Reports)
Abstract Previous work indicates that SARS-CoV-2 virus entry proteins angiotensin-converting enzyme 2 (ACE-2) and the cell surface transmembrane protease serine 2 (TMPRSS-2) are regulated by sex hormones. However, clinical studies addressing this association have yielded conflicting results. We sought to analyze the impact of sex hormones, age, and cardiovascular disease on ACE-2 and TMPRSS-2 expression in different mouse models. ACE-2 and TMPRSS-2 expression was analyzed by immunostaining in a variety of tissues obtained from FVB/N mice undergoing either gonadectomy or sham-surgery and being subjected to ischemia–reperfusion injury or transverse aortic constriction surgery. In lung tissues sex did not have a significant impact on the expression of ACE-2 and TMPRSS-2. On the contrary, following myocardial injury, female sex was associated to a lower expression of ACE-2 at the level of the kidney tubules. In addition, after myocardial injury, a significant correlation between younger age and higher expression of both ACE-2 and TMPRSS-2 was observed for lung alveoli and bronchioli, kidney tubules, and liver sinusoids. Our experimental data indicate that gonadal hormones and biological sex do not alter ACE-2 and TMPRSS-2 expression in the respiratory tract in mice, independent of disease state. Thus, sex differences in ACE-2 and TMPRSS-2 protein expression observed in mice may not explain the higher disease burden of COVID-19 among men.